Enterprises’ effectiveness: A study on structure, focus and enterprises’ outcomes - Matea Zlatković Radaković (Anali Ekonomskog fakulteta u Subotici, 2024)
To obtain and retain high performances enteprises are faced with expectations and demands of variouty constituencies which are inheretly important part of their functioning. The research purporse is to validated the psychometric properties of widely used holistic view of enterprises performance defined by competing value framework in context of enterprises in transition economy such as Republic of Srpska, Bosnia and Herzegovina. To fulfill research aim a quantitative, cross-sectional research design was carried to collect and analyse data from 224 organizational representatives. Covariance-based structural equations modeling is used to test the competing values approach and, if needed, to modify a measurement scale that identifies the extent to which sampled enterprises use the measurement criteria of each aspect of effectiveness to validated effectiveness of enterprises. All models of effectiveness have acceptable reliabilities and convergent validity and discriminant validity are established. Model fit measures indicate acceptable goodness-of-fit. Academics and managers may consider to use these measures of effectiveness to better understand the performance/effectiveness phenomenon and have better insight into possibilities for enhancement of different aspects of effectiveness. This study represents the first attempt to investigate and validate the presence of mutual dependence of certain aspects of effectiveness according to competing values approach in specific research context.